Endothelial nitric oxide synthase Glu298Asp gene polymorphism in the cases of idiopathic thrombocytopenic purpura - Akarsu, Saadet; Arslan, Feyzullah Necati; Erol, Deniz (Korean Soc Hematology, 2022)
Background Nitric oxide (NO) can induce apoptosis in megakaryocytes. Stimulatory function of NO on platelet production may be important in the pathophysiology of idiopathic thrombocytopenic purpura (ITP). NO is produced by three isoforms of NO synthase (NOS). The endothelial nitric oxide synthase (eNOS) isoform has been detected in platelets. Polymorphism of the eNOS gene, which supplies NO synthesis, changes the functions of this enzyme. In this study, the role of eNOS Glu298Asp gene polymorphism in etiopathogenesis, its course, and treatment of ITP was investigated. Methods Sixty-six patients [51 newly diagnosed ITP (ND-ITP), 15 chronic ITP (CH-ITP), and 60 healthy controls (HC)] were enrolled in this study. Results In all patients, the frequency of the GT genotype was 48.5%. The frequency of the GG genotype was determined to be 40.9% and the TT genotype was 10.6%. The most common allele in all patients was the G allele. eNOS Glu298Asp gene polymorphism might be a risk factor in the etiopathogenesis of ITP. Patients with the GG genotype were thought to have a high intention for CH-ITP. Patients with the GG genotype responded effectively to medical treatment using IVIG therapy. The presence of the G allele was observed to have a positive effect on the medical treatment of patients with CH-ITP, whereas the T allele exhibited a negative effect. Conclusion In the present study, a significant correlation was found between ITP and eNOS Glu298Asp gene polymorphism. This correlation suggested that eNOS Glu298Asp gene polymorphism might be a risk factor in the ethiopathogenesis of ITP.
Keywords: Idiopathic thrombocytopenic purpura (ITP); Endothelial nitric oxide synthase (eNOS); Glu298Asp gene; Polymorphism